2016
DOI: 10.1164/rccm.201502-0407oc
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow–derived Cells Contribute to the Pathogenesis of Pulmonary Arterial Hypertension

Abstract: Our data show that BM cells played a key role in PAH pathogenesis and that the transplanted BM cells were able to drive the lung phenotype in a myeloablative transplant model. Furthermore, the specific cell types involved were derived from hematopoietic stem cells and exhibit dysfunction long before the development of lung pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 62 publications
1
58
0
1
Order By: Relevance
“…There is evidence from several groups that bone marrow cells alone are sufficient to drive PAH, including our finding that control bone marrow-derived stem cells can reduce the PAH phenotype when transplanted into lethally irradiated Bmpr2 mutant mice (63,64). This suggests the future possibility of autologous bone marrow transplantation after edited correction of stem cells as a therapeutic possibility; that is, correction of the mutation from the stem cells of a BMPR2 mutation carrier with PAH could be a therapeutic approach (Figure 3) (64). However, this is technically challenging for a variety of reasons, including the need for high efficiency, the need to avoid off-target effects, and the need for high speed to avoid genomic instability or terminal differentiation of stem cells.…”
Section: C/fpomentioning
confidence: 85%
“…There is evidence from several groups that bone marrow cells alone are sufficient to drive PAH, including our finding that control bone marrow-derived stem cells can reduce the PAH phenotype when transplanted into lethally irradiated Bmpr2 mutant mice (63,64). This suggests the future possibility of autologous bone marrow transplantation after edited correction of stem cells as a therapeutic possibility; that is, correction of the mutation from the stem cells of a BMPR2 mutation carrier with PAH could be a therapeutic approach (Figure 3) (64). However, this is technically challenging for a variety of reasons, including the need for high efficiency, the need to avoid off-target effects, and the need for high speed to avoid genomic instability or terminal differentiation of stem cells.…”
Section: C/fpomentioning
confidence: 85%
“…23,29,30 Engraftment of serotonin 2B receptordeficient BM in WT mice protected against the development of hypoxia-induced pulmonary vascular remodeling and elevation of RVSP in mice. 29 In a Bmpr2 mutant model that spontaneously developed PH without RV remodeling, pulmonary vascular remodeling and elevation of RVSP were shown to be dependent on the BM.…”
Section: Discussionmentioning
confidence: 99%
“…29 In a Bmpr2 mutant model that spontaneously developed PH without RV remodeling, pulmonary vascular remodeling and elevation of RVSP were shown to be dependent on the BM. 30 Also, xenograft studies with BM isolated from patients showed that PAH BM induced pathological RV hypertrophy. 23 In a prior study, BM from patients with germline CAV-1 mutation led to a more severe phenotype in the xenografted mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have confirmed the ability of BMPR2 gene therapy to improve PAH in animal models by increasing Smad1/5/8 signalling and possibly by increasing nitric oxide production in human pulmonary endothelial cells [85]. YAN et al [86] showed that myeloablative radiation followed by transplantation of donor stem cells from mice with normal BMPR2 into mice with BMPR2 mutations prevented the development of PH. Although these pre-clinical data are promising, there are likely to be significant challenges in translating BMPR2 gene therapy to humans with our current limitations in vector delivery to the pulmonary endothelium, immunogenicity and uncertainty regarding whether increasing BMPR-II expression results in sustainable long-term improvements in PAH.…”
Section: Is Precision Medicine Ready For Use In Pah/ph?mentioning
confidence: 94%